Finance and Development, March 1975. (Finance and Development; Finance and Development ;, 1975)
This paper reviews the self-help housing project in El Salvador. The paper highlights that projects like this one become community efforts in a real sense. The families participate in road building, construction, digging trenches, and pipe-laying, under supervision. The Fundacion Salvadorena de Desarrollo y Vivienda Mi'nima (FSVM) is the executing agency in this self-help project involving a USD 6 million International Development Association (IDA) credit and a USD 2.5 million loan from the World Bank to the government of El Salvador. The FSVM has already completed about 1,020 fully serviced lots for families with monthly incomes below USD 120.